2018
DOI: 10.1177/0194599818789132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the NSQIP Surgical Risk Calculator in Predicting Microvascular Head and Neck Reconstruction Outcomes

Abstract: Objective This study evaluated the accuracy of the Surgical Risk Calculator (SRC) of the ACS NSQIP (American College of Surgeons National Surgical Quality Improvement Program) in predicting head and neck microvascular reconstruction outcomes. Study Design Retrospective analysis. Setting Tertiary medical center. Subjects and Methods A total of 561 free flaps were included in the analysis. The SRC-predicted 30-day rates of postoperative complications, hospital length of stay (LOS), and rehabilitation discharge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ma et al analyzed 561 head and neck free flaps and found that, although SRC demonstrated a Brier score <0.01 for urinary tract infection and renal complications, no complications were associated with a C statistic >0.8 indicating inadequate test performance. Furthermore, LOS was not accurately predicted by the SRC in their study …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Ma et al analyzed 561 head and neck free flaps and found that, although SRC demonstrated a Brier score <0.01 for urinary tract infection and renal complications, no complications were associated with a C statistic >0.8 indicating inadequate test performance. Furthermore, LOS was not accurately predicted by the SRC in their study …”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, LOS was not accurately predicted by the SRC in their study. 11 Limitations to the NSQIP SRC calculator are well known. 19 Notably, it was developed as a universal calculator and does not factor in many aspects distinct to head and neck surgery patients such as flap loss, speech and swallowing symptoms, and tracheostomy dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prasad et al concluded, in a cohort of 98 patients, that ACS-NSQIP risk calculator was a poor predictor of perioperative complications following major head and neck operations [28]. Other two recent studies pertaining to microvascular head and neck reconstruction showed poor prediction performance of ACS-NSQIP [29,30]. In addition, Schneider et al have added total laryngectomy to the list of complex procedures for which the NSQIP risk calculator may not be as accurate in predicting postoperative adverse events [31].…”
Section: Discussionmentioning
confidence: 99%